Model Pelaksanaan Mediasi Melalui Pranata Tutur Pada Masyarakat Batak Muslim Tapanuli Selatan - ANWAR SADAT; AHMAD LAUT HASIBUAN (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2016)
This article examines the contribution of local culture or costum (adat)  in family conflict management among Batak Muslims in Southern Tapanuli.  It is very common that marital conflicts ended up in the court. To avoid engaging court to judge a marital conflict within a family,   Batak Muslim in Southern Tapanuli utilized Dalihan Na Tolu custom to resolve the problem. Batak Muslims in Southern Tapanuli often mediated the conflicting couples through a process, which is referred to as Tutur. By utilizing anthropological and socio-legal approach, the authors analyze the effectiveness in utilizing Tutur tradition among Batak Muslim family and argue that local costum such as Tutur has still played an effec- tive role in preventing divorce as well as in reconciling conflicting family mem- bers.